Geotouristic excursion to selected historical mining sites developed by Slovak and German miners in the Gelnica-Smolník region, Slovakia - Rybár, Pavol; Sasvári, Tibor; Hvizdák, Ladislav; Hvizdáková, Jana; Baláž, Bartolomej (Geotourism/Geoturystyka, 2025)
The following paper summarizes the history of Gelnica, Smolník and Rožňava gold, silver, copper and iron orefields in Eastern Slovakia, which have been mined since the Medieval ages by of Slovak and German miners. In Gelnica, where mining operations date back to the XIIth century, massive quartz-sideritechalcopyrite veins with Fe-dolomite, pyrite and tetrahedrite (with silver) cut Lower Devonian phyllites and porphyroids. In Smolník, where copper mining has commenced in the first half of the XIIIth century followed by gold, then silver and iron ore exploitation, 10-11 pyrite-chalcopyrite ore horizons are hosted in Silurian phyllites. In Rožňava mining operations for iron, silver, gold and copper ores have been known since the XIIIth century and have lasted until 1992. Over 40 ore veins discovered in this field contain mostly siderite although quartz-siderite-sulphide paragenesis with Ag-bearing tetrahedrite was also observed. In all three mining districts there are numerous objects of mining heritage and other valuable historical monuments, reflecting the wealth of old Slovak mining towns.